Drug-Induced Psychosis: How to Avoid Star Gazing in Schizophrenia Research by Looking at More Obvious Sources of Light - Paparelli, Alessandra; Di Forti, Marta; Morrison, Paul D.; Murray, Robin M. (Frontiers in Behavioral Neuroscience, 2011)
The prevalent view today is that schizophrenia is a syndrome rather than a specific disease. Liability to schizophrenia is highly heritable. It appears that multiple genetic and environmental factors operate together to push individuals over a threshold into expressing the characteristic clinical picture. One environmental factor which has been curiously neglected is the evidence that certain drugs can induce schizophrenia-like psychosis. In the last 60 years, improved understanding of the relationship between drug abuse and psychosis has contributed substantially to our modern view of the disorder suggesting that liability to psychosis in general, and to schizophrenia in particular, is distributed trough the general population in a similar continuous way to liability to medical disorders such as hypertension and diabetes. In this review we examine the main hypotheses resulting from the link observed between the most common psychomimetic drugs (LSD, amphetamines, cannabis, PCP) and schizophrenia.